PAUD BERWAWASAN INTEGRATIF (Difusi Inovasi Ilmu & Agama ke dalam Proses Pembelajaran Pendidikan Anak Usia Dini) - Suyadi, Suyadi (Yinyang: Jurnal Studi Islam Gender dan Anak, 2016)
The effort to implement Islamic values in the learning process of early childhood education has resulted in various practices. Many foundations, mass organizations, religious, and even political organizations participate in establishing education institutions for early childhood education (PAUD). For instance, Muhammadiyah establishes ABA Nursery School, NU establishes Raudhatul ‘Athfal (RA), private foundations establish their own nursery schools (such as Tunas Melati Nursary School, etc.), as well as what Justice and Welfare Party (PKS) establishes, i.e. Islam-integrated educations institutions of nursery schools. All of the varieties are done to insert Islamic values to the learning process, which is considered to be better. However, the practice of inserting Islamic values in early childhood education is often trapped in two basic practices, i.e. the use of religious symbols and cognitive aspects of religion. To anticipate that condition, this article is trying to formulate a diffusion of innovation in implementing Islamic values in the learning process in early childhood education integratedly and interconnectedly. This means that teaching religion includes not only religious knowledge but also science in the perspective of religion. To formulate the diffusion of innovation, this article applied Michael Fullan’s theory of change as found in his book entitled The Meaning of Education Change and Roger’s adoption pattern. Based on the theories, this article suggests a new formula of developing early childhood education in the future, especially for nursery schools.